(untitled) (Bangladesh Journal of Animal Science, 2014)
A survey was conducted to explore prevalence and risk factors of diverse hoof disorders on dairy cows at Chittagong and Patuakhali, Bangladesh from June 2012 to February 2013. About 2103 cows were examined from where 497 cases identified having fissure (37%), crack (19%), partially broken (19%), swollen hoof (16%) and multiple disorders (9%) in backyard dairy cows whereas 37%, 17%, 20%, 20% and 6% in commercial cows, respectively. Significantly higher prevalence (p<0.05) was recorded in cows reared under concrete floor (68.4%) compared to brick (13.27%) and concrete with rubber bedding (18.3%). Other major conventional risk factors were season, age, milk yield and washing practiced on floor though the results were not significant (p>0.05). The study has remarked frequency of hoof diseases in the survey areas along with factors causing risk to dairy cows. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20714 Bang. J. Anim. Sci. 2014. 43 (2): 132-137